Penemuan Hukum dalam Penilaian Unsur Pidana terhadap Jasa Profesional dalam Tindak Pidana Korupsi: Studi Kasus Putusan Bebas Amsal Sitepu - Muhammad Farhan Putra (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines judicial law-finding in Decision No. 171/Pid.SusTPK/2025/PN Mdn (1 April 2026), which acquitted Amsal Christy Sitepu of corruption charges involving videography services in Karo Regency. The prosecution alleged state losses of approximately Rp202,000,000 based on the gap between contract value and auditor estimates. The court found no standardized pricing benchmark in the videography industry, rendering the loss calculation speculative and the corruption elements unproven. The central issue is the inability of Article 2(1) of the Anti-Corruption Law to capture non-standardized creative services, making judicial law-finding a corrective mechanism against overcriminalization. This study recommends formulating state loss assessment guidelines for non-standardized service sectors.